Clostridioides difficile infection: a comprehensive review for primary providers - Cortés Pedro; Bi Yan; Stancampiano Fernando; Valery Jose R.; Cooper Jane H.; Harris Dana M. (Sciendo, 2021)
Clostridioides difficile infection (CDI) is an issue of great concern due to its rising incidence, recurrence, morbidity and impact on healthcare spending. Treatment guidelines have changed in the last few years, and new therapies are being considered. This is a practical review for the primary care practitioner of the latest guidelines for CDI diagnosis, treatment, and emerging therapies.